DEKONSTRUKSI CITRA PEREMPUAN DALAM KUMPULAN CERPEN JANGAN PULANG JIKA KAMU PEREMPUAN KARYA RIYANA RIZKI - Ahmad Burhanuddin; Ririe Rengganis; Tengsoe Tjahjono (Haluan Sastra Budaya, 2023)
Literary works generally discuss the social lives of society, one of which is about women. The reason why women's problems in literary works have come to the attention of the author is based on feelings of love and empathy for the world of Indonesian women, which since the time of Balai Pustaka until now women have still been subordinate to men. man. However, in the collection of short stories, Jangan Pulang Jika Kamu Perempuan, apart from studying women's resistance, they also discuss the deconstruction of women's images. This type of research is a qualitative research. The data collection technique in this research is in the form of library technique. From the research results obtained three deconstructions of the image of women contained in the collection of short stories Jangan Pulang Jika Kamu Perempuan by Riyana Rizky, namely women and customary law, Women and the Character of Stepmothers and Women and Freedom.